Seeing the unseen learner: designing and using social media to recognize children's science dispositions in action. Issue 2 (2nd April 2016) - Ahn, June; Clegg, Tamara; Yip, Jason; Bonsignore, Elizabeth; Pauw, Daniel; Gubbels, Michael; Lewittes, Charley; Rhodes, Emily
Abstract : This paper describes the development of ScienceKit, a mobile, social media application to promote children's scientific inquiry. We deployed ScienceKit in Kitchen Chemistry ( KC ), an informal science program where children learn about scientific inquiry through cooking. By iteratively integrating design and implementation, this study highlights the affordances of social media that facilitate children's trajectories of disposition development in science learning. We illuminate how the technological and curricular design decisions made in ScienceKit and KC constrain or expand the types of data we can collect and the actionable insights about learning we can recognize as both educators and researchers. This study offers suggestions for how information gleaned from social media tools can be employed to strengthen our understanding of learning in practice, and help educators better recognize the rich actions that learners undertake, which may be easily overlooked in face-to-face situations.